15N study of the reactivity of atmospheric nitrogen in four mountain forest catchments (Czech Republic, central Europe). (May 2020) - Buzek, Frantisek; Cejkova, Bohuslava; Jackova, Ivana; Kram, Pavel; Oulehle, Filip; Myska, Oldrich; Curik, Jan; Veselovsky, Frantisek; Novak, Martin
Abstract: Reactivity of atmospherically deposited nitrate (NO3 − ) and ammonium (NH4 + ) was investigated in three mountain forest catchments and one ombrotrophic peat bog located in the northern Czech Republic. The study sites are characterized by moderate to high N pollution rates that are currently decreasing. Monitoring of hydrodynamic data and catchment hydrochemistry (precipitation, soil solutions and runoff) was complemented by δ 15 N analyses of dissolved inorganic N (NO3 −, NH4 + ). Measured δ 15 N data were used to calculate the extent of biogeochemical reactions and to construct N mass balances. Two-component models of runoff generation were developed using hydrological and δ 18 O–H2 O data on local precipitation, runoff, and soil waters collected by lysimeters. Catchment discharge was formed by groundwater (60–80%) and storm precipitation (40–20%), with minimal time lags. Groundwater had a diluting effect on reactions proceeding in the soil zone, including nitrification and denitrification. The rates of nitrification were estimated by comparing the δ 15 N values of atmospheric input and soil water, while the rates of denitrification were derived from the differences in the δ 15 N values of soil water and stream discharge. The Ν isotope effect of mineralisation of organic N was assessed by comparing δ 15 N values of soil and soil extracts. Nitrogen release from the catchments was controlled by temperature-dependent seasonality of soil reactions. Atmospheric N entered the runoff directly only during a short late winter - early spring period, accounting for approximately 10% of the total N input. Important inputs of mineralised organically cycled soil N were observed at the beginning and the end of the growing season, with measurable denitrification occurring during the same time periods. The measured apparent N isotope fractionations were significantly lower than previously published values (−3 to −14‰ vs. −30‰ for nitrification, and −3 vs. −20‰ for denitrification). Lower 15 N fractionations originated both from the dilution effect of groundwater on stream discharge and from the depletion of available ammonium during nitrification reactions. Denitrification proceeding during recharge of the groundwater body was estimated from the difference in the δ 15 N values of NO3 − in precipitation and groundwater. Graphical abstract: Image 1 Highlights: Runoff generation models based on δ 18 O–H2 O data were used to quantify contributions of groundwater and rainfall to catchment discharge. Proceeding reactions were estimated from catchment hydrochemistry data plus δ 15 N analyses of NH4 + and NO3 − in precipitation, soil water, and stream discharge. Nitrogen release from catchments was controlled by the seasonality of soil processes: high rate during the growing season, low rate during the dormant season. The apparent 15 N fractionation was lower than published data because of a groundwater-dilution effect in discharge and depletion of the ammonium pool. Calculated N loss via denitrification varied from 0.3 to 1.3 kg N ha −1 y −1, corresponding to 3 to 23% of total N deposition.